2023
DOI: 10.3390/antiox12040894
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Metallothioneins as a Target for Neuroprotection in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is characterized by motor symptoms based on a loss of nigrostriatal dopaminergic neurons and by non-motor symptoms which precede motor symptoms. Neurodegeneration accompanied by an accumulation of α-synuclein is thought to propagate from the enteric nervous system to the central nervous system. The pathogenesis in sporadic PD remains unknown. However, many reports indicate various etiological factors, such as oxidative stress, inflammation, α-synuclein toxicity and mitochondrial impair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 183 publications
0
8
0
Order By: Relevance
“…Functional differences between organ systems, potentially stemming from differences in adrenergic and glucocorticoid receptor distribution or activation, are causing tissue-speci c responses to the ozone stressor (Kalinyak et al, 1987;Paik et al, 2020). The few genes commonly changed by ozone in all tissues include several responsible for responding to cell stress, including Cdkn1a, involved in DNA damage response and cell cycle progression (Dutto et al, 2015), Gpatch4, important in nucleosome response to stress (Hirawake-Mogi et al, 2021), Mt1m and Mt2a, responders to metal and non-metal stress (Miyazaki & Asanuma, 2023), and Pcdh12, critical in cell adhesion (Rampon et al, 2005). Because ozone itself is unlikely to translocate beyond the lung upon inhalation, the conserved response across diverse organ systems is likely due to a systemic stress response.…”
Section: Discussionmentioning
confidence: 99%
“…Functional differences between organ systems, potentially stemming from differences in adrenergic and glucocorticoid receptor distribution or activation, are causing tissue-speci c responses to the ozone stressor (Kalinyak et al, 1987;Paik et al, 2020). The few genes commonly changed by ozone in all tissues include several responsible for responding to cell stress, including Cdkn1a, involved in DNA damage response and cell cycle progression (Dutto et al, 2015), Gpatch4, important in nucleosome response to stress (Hirawake-Mogi et al, 2021), Mt1m and Mt2a, responders to metal and non-metal stress (Miyazaki & Asanuma, 2023), and Pcdh12, critical in cell adhesion (Rampon et al, 2005). Because ozone itself is unlikely to translocate beyond the lung upon inhalation, the conserved response across diverse organ systems is likely due to a systemic stress response.…”
Section: Discussionmentioning
confidence: 99%
“…At the level of the nervous system, these proteins are present in glial cells and neurons and appear to have a protective effect against the neurotoxicity of some heavy metals such as lead, mercury and cadmium. It has been suggested that metallothioneins may be a way to prevent or treat neurodegenerative diseases (Juárez-Rebollar et al, 2017 ; Manso et al, 2011 ; Miyazaki & Asanuma, 2023 ; Samuel et al, 2021 ). In relation to this, MT2A is considered a key player in the maintenance of immune homeostasis (Jakovac et al, 2013 ) and its involvement as a neuroprotective factor has been described in different neurodegenerative diseases such as Parkinson's disease (Miyazaki et al, 2013 ), Alzheimer's disease (Chung et al, 2010 ), or amyotrophic lateral sclerosis (Brandebura et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, MTs' interaction with ferritin, a protein involved in iron storage, is suggested to have a potential impact on iron release under oxidative conditions. In the context of Parkinson's disease (PD), where iron accumulation is linked to ferroptosis and disease pathogenesis, understanding the interplay between MTs and iron metabolism may offer insights into potential neuroprotective strategies [119].…”
Section: Targeted Therapy For Ferroptosismentioning
confidence: 99%